The regional model of three-level system of of medical social monitoring of children and adolescents: the pilot project in the Republic of Tatarstan - Al'bitskii, V Iu; Ustinova, N V; Farrakhov, A Z; Shavaliev, R F; Kulikov O V; Plaksina, L V (Problemy sotsial'noi gigieny, zdravookhraneniia i istorii meditsiny, 2014)
The absence of system of medical social monitoring of children being in difficult life situations is one of main causes of preventable losses of health and life of children and adolescents. The plan of activities of the working group No3 under the Coordination council under the President of the Russian Federation of the national strategy realization of actions in interest of children for 2012-2017 includes a point: "The development and implementation of standard model of medical social monitoring of children and adolescents in the subjects of the Russian Federation". The implementation of this task is assigned to the Department of social pediatrics of The research center of children health of Moscow and the Ministry of Health of the Republic of Tatarstan. The research methods included analysis and generalization of advanced experience of medical social monitoring of children population; expertise technique; modeling. The regional model of three-level system of medical social monitoring of children population is developed and implemented. The model includes level I (consulting rooms of medical social care of children polyclinics, feldsher obstetric stations, first-aid centers), level II--inter-municipal (departments of medical social monitoring in central district hospitals, medical institutions, clinical diagnostic centers) and level III--regional (the Republican center of medical social monitoring of children and adolescents). The immediate tasks necessary for effective functioning of system of medical social monitoring were determined. Within the framework of implementation of the pilot project the legal and normative legislative acts were developed to regulate functioning of regional model of three-level system of medical social care. The other documents necessary for effective functioning of this system were elaborated. The practical significance of this system is in the implementation of effective three-level model of medical social monitoring of children and adolescents supporting decrease of morbidity, mortality and "risk behaviors" suicidal included. The model is to prevent child neglect and homelessness and cruel treatment of children and adolescents.